The Genesis debate persistent questions about Creation and the Flood - Youngblood, Ronald F. (Grand Rapids, MI Baker, 1990)
Includes bibliographical references.
Keywords: Bible. O.T. Genesis I-XI -- criticism, interpretation, etc; Creationism; Deluge